2009
DOI: 10.1007/s10640-009-9317-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Links Between Innovation and Diffusion: Adoption of NOX Control Technologies at US Coal-fired Power Plants

Abstract: While many studies have looked at innovation and adoption of technologies separately, the two processes are linked. Advances (and expected advances) in a single technology should affect both its adoption rate and the adoption of alternative technologies. This paper combines plant-level data on US coal-fired electric power plants with patent data pertaining to NO X pollution control techniques to study this link. As in other studies of environmental technologies, the effect of other explanatory variables is dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 30 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…These studies fall into five sets. One set assesses the effect of environmental regulation on firms' competitiveness, innovation activities, employment, or productivity (Jaffe et al 1995;Jaffe and Palmer 1997;Popp 2006;Berman and Bui 2001a,b;Greenstone 2002;Managi et al 2005). While evidence for employment and productivity is mixed, these studies generally find environmental regulation has had no effect on competitiveness and a positive effect on innovation activities.…”
Section: Relationship Between Environmental Regulation and Financial mentioning
confidence: 99%
“…These studies fall into five sets. One set assesses the effect of environmental regulation on firms' competitiveness, innovation activities, employment, or productivity (Jaffe et al 1995;Jaffe and Palmer 1997;Popp 2006;Berman and Bui 2001a,b;Greenstone 2002;Managi et al 2005). While evidence for employment and productivity is mixed, these studies generally find environmental regulation has had no effect on competitiveness and a positive effect on innovation activities.…”
Section: Relationship Between Environmental Regulation and Financial mentioning
confidence: 99%
“…The hazard rate is defined as the conditional probability of adoption at time t, given that the firm has not adopted before t. 9 As is common in the adoption literature (e.g., Karshenas and Stoneman, 1993;Popp, 2010;Kerr and Newell, 2003), we estimate a proportional hazard model of the form…”
Section: Model Of the Investment Decisionmentioning
confidence: 99%
“…For the US, the adoption of NO x control technologies have been analyzed by Popp (2010) who looked at investment at coal-fired power plants. He found that expectations of future technological advances slow down the diffusion of existing combustion modification technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we discuss the research that compares different environmental policy instruments with respect to their effects on technology diffusion. Popp (2010) studies the link between innovation of NO X pollution control technologies and their adoption by US coal fired power plants. The paper finds that the key explanatory variable for adopting pollution control technologies is environmental regulations.…”
Section: Evidence On Policy Instrumentsmentioning
confidence: 99%